Le repas de noces dans la Crète de la Vénétocratie - Georgia K. Varzelioti (Cahiers Balkaniques)
In 1609, noblewoman Pandoussa Mezeri, widow of the Cretan physician Victor Mezeris, began to keep records of the daily management of her household. The librο dei conti, written in first person singular, in the form of a journal, is located at the State Archives of Venice and represents a valuable source of information on daily life in Candia during the first half of the 17th century. During the 11 years that followed, the weddings of the five daughters of the Mezeri family took place and Mezeri recorded in great detail the preparations, including shopping for a variety of ingredients, local as well as imported from other areas under Venetian rule and from Venice itself. This “journal”, is a unique source of information on the history of food and cuisine culture, in that it describes the kinds, the origins the quality and the prices of foodstuffs, but also the local nutrition traditions and customs with their symbolic meaning in the social context, as well as the mindset and habits marking the multicultural urban civilization in the capital city of the Regno di Candia.